Christoph Fink : Atlas of Movements = Atlas der Bewegingen : Movement # 59 : epilogue The Cleveland Walks = De Clevelandwandelingen, Movement # 60 from Brussels City Center to Brussels Airport, Movement # 61 : The Leuven Walks = De Leuvenwandelingen, Movement # 62 Trans-Alpine Attempt # 6 : Ghent-Geneva, Movement # 63 : Ouverture Brussels-New York-Cleveland-New York-Brussels. - Exhibition. Christoph Fink : Movement #61, The Leuven Walks, Movement #59 The Cleveland Walks. Museum Vander Kelen-Mertens Leuven. 2003-11-21. 2003-02-02 (Gent Leuven : MERZ / Luc Derycke & Co. Gent Museum Vander Kelen-Mertens Leuven, 2003)
Christoph Fink's 'Atlas of Movements' is a now 3 volumes' series of cartographic studies that inventorize what he calls his 'source materials', materials that construct his drawings, sculptures and sound pieces.
At first glance, the presentation of material seems scientific, almost quantifiable, dry, and a tad overwhelming. The number of annotated and translated notes, as well as Fink's intricate legend, point to a clear intent to communicate, revealing a prosaic and sometimes humorous narrative that's less about a place than about the interval stages of moving from place to place. For example, Fink's chronometered" notes, as he calls them, revel in the mundane, his shorthand descriptions ranging from accounts of the weather to observations about train schedules to descriptions of physical exertion and the finding of sustenance.
By foot, bicycle, car, train, and plane, Fink moves from place to place, taking notes every step of the way. His paper landscapes or overlay of sketches, carbon-copy drawings, photographs, sound recordings, paper cutouts, maps, and statistical notations presented in different shapes, sizes, and colors are culled from hundreds of notes scrawled in a small carbon notebook. After sorting through and organizing his array of data, Fink translates these notes into a visual language, arranging the results into a kind of index or chorograph, a practice that combines surveying, geometry, and the making of 'graphic images' (mimetic and conventional signs, color coding, and calligraphy) with the production of numerical and alphabetic inscriptions and texts.'
biog. p. 353
Engels
Nederlands
boek
Keywords: Fink, Christoph